2001
DOI: 10.1016/s0893-133x(00)00225-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurofunctional Effects of Developmental Alcohol Exposure in Alcohol-Preferring and Alcohol-Nonpreferring Rats

Abstract: The neurofunctional effects of developmental alcohol exposure (3% v/v solution from day 15 of gestation to day 7 after parturition) have been investigated in Sardinian alcoholpreferring (sP) and alcohol-nonpreferring (sNP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
22
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 45 publications
8
22
0
Order By: Relevance
“…A recent study in the present series has shown that offspring of Sardinian alcohol-preferring (sP) and Sardinian alcohol-nonpreferring (sNP) rats, selectively bred (from Wistar rats) for opposite alcohol preference and consumption, exhibited a different behavioral profile in response to perinatal exposure to this drug of abuse, at doses below those associated with gross malformations and/or overt neurotoxic effects (Tattoli et al 2001). Specifically, alcohol exposure significantly reduced the rate of ultrasonic emission in sP male pups, whereas it did not influence this indicator of emotional reactivity in sNP neonates.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…A recent study in the present series has shown that offspring of Sardinian alcohol-preferring (sP) and Sardinian alcohol-nonpreferring (sNP) rats, selectively bred (from Wistar rats) for opposite alcohol preference and consumption, exhibited a different behavioral profile in response to perinatal exposure to this drug of abuse, at doses below those associated with gross malformations and/or overt neurotoxic effects (Tattoli et al 2001). Specifically, alcohol exposure significantly reduced the rate of ultrasonic emission in sP male pups, whereas it did not influence this indicator of emotional reactivity in sNP neonates.…”
mentioning
confidence: 81%
“…Specifically, alcohol exposure significantly reduced the rate of ultrasonic emission in sP male pups, whereas it did not influence this indicator of emotional reactivity in sNP neonates. Therefore, it appeared of interest to further investigate the effects of developmental alcohol exposure in the sP and sNP lines, using both some of the offspring from litters of the study just mentioned (Tattoli et al 2001) and the offspring of additional litters. As in the previous study, the aim was to investigate the consequences of a low level alcohol exposure clearly under the threshold for gross toxic and/ or teratogenic effects, but still capable to provide information on the pathogenesis of ARNDs falling short of the fully fledged Fetal Alcohol Syndrome (FAS).…”
mentioning
confidence: 99%
See 3 more Smart Citations